Flipbook Maker-Based Teaching Materials of thematic Learning for grade II Elementary School Students - Ni Kadek Putriani; Maria Goreti Rini Kristiantari (Universitas Pendidikan Ganesha, 2022)
Currently, there are still many schools that only focus on textbooks without the innovation and creativity of teachers in preparing teaching materials, so that it is very influential for the learning process. The purpose of this study was to develop design and feasibility of teaching materials based on Flipbook Maker application. The test subjects in this study were content experts, designs, instructional medias, and second grade elementary school students. This study uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). Data were collected using observation, interview and questionnaire methods. The data analysis technique used is descriptive qualitative and quantitative descriptive analysis techniques. However the results of data analysis as follows. (1) Design of Flipbook Maker-based e-teaching materials which consists of five stages, namely the analysis stage (Analyze), the design stage (Design), the development stage (Development), the implementation stage (Implementation), and the evaluation stage (Evaluations). (2) teaching materials which are based on the Flipbook Maker have a good quality based on the results of the review of subject matter experts showing a score of 96%, the results of the learning design expert review showing a score of 100%, the results of the media expert review showing a score of 95%, the results of the individual test showing a score of 97.6% and the results of the small group trial showed a score of 99% so that the overall score showed a very good category. It is concluded that flipbook maker-based teaching materials are suitable used for learning.